Cardiac gene therapy: methods and protocols - Ishikawa, Kiyotake (Methods in molecular biology, 2017)
Current Methods in Cardiac Gene Therapy: Overview -- Silencing Genes in the Heart -- Generation of Efficient miRNA Inhibitors Using Tough Decoy Constructs -- Efficient Genome Editing in Induced Pluripotent Stem Cells with Engineered Nucleases In Vitro -- Direct Cardiac Reprogramming as a Novel Therapeutic Strategy for Treatment of Myocardial Infarction -- Production and Characterization of Vectors Based on the Cardiotropic AAV Serotype 9 -- Cell-Based Measurement of Neutralizing Antibodies Against Adeno-Associated Virus (AAV) -- Synthesis of Modified mRNA for Myocardial Delivery -- Exosomes-Based Gene Therapy for MicroRNA Delivery -- Lipidoid mRNA Nanoparticles for Myocardial Delivery in Rodents -- Gene Transfer in Isolated Adult Cardiomyocytes -- Gene Transfer in Cardiomyocytes Derived from ES and iPS Cells -- Gene Transfer to Rodent Hearts In Vivo -- Ultrasound-Targeted Microbubble Destruction for Cardiac Gene Delivery -- A Needleless Liquid Jet Injection Delivery Approach for Cardiac Gene Therapy -- Cardiac Gene Delivery in Large Animal Models: Antegrade Techniques -- Direct Myocardial Injection of Vectors -- Selective Pressure-Regulate Retroinfusion for Gene Therapy Application in Ischemic Heart Disease -- Cardiac Gene Delivery Using Recirculating Devices -- Molecular Cardiac Surgery with Recirculating Delivery (MCARD): Procedure and Vector Transfer -- Gene Delivery for the Generation of Bioartificial Pacemaker -- Gene Therapy for Post-Infarction Ventricular Tachycardia -- MicroRNA Delivery Strategies to the Lung in a Model of Pulmonary Hypertension -- Inhaled Gene Transfer for Pulmonary Circulation.